(3GdCe```f GdEb`dj`e``js - (3GdLejdj(B, (3YHO GdQMef CMeOs ((3YeGfs (3OGQ LdjS GdReGfs, 2023)
(3jJfGhd gPG GdcJGH eaghe GdCef GdEbdjej HTcd Yejb, eSJYQVkG eLehYI hGSYI ef GdeJZjQGJ hGdfXQjGJ GdJj JDKQ Ydi gPG Gdeaghe(B. (3jbOe GdcJGH JMdjdkG ObjbkG ddCef GdEbdjej aj efGWb eNJdaI ef GdYGde, eKd GdhWf GdYQHj hGdHMQ GdcGQjHj hGdTQb GdChSW(B. (3ceG jSJcTa GdcJGH GdYdGbI Hjf GdCef GdEbdjej hGdGSJQGJjLjGJ GdOhdjI, dG SjeG GSJQGJjLjGJ Gdbhi GdcHQi eKd GdhdGjGJ GdeJMOI(B. (3HGdEVGaI Edi Pdc, jSdW GdcJGH GdVhA Ydi GdJMOjGJ GdJj JhGLg GdCef GdEbdjej aj efGWb eYjfI, eKd GdCReI GdNdjLjI, hjbJQM QDi eSJbHdjI dJYRjR GdJYGhf GdCefj GdEbdjej(B. (3HTcd YGe, jYJHQ gPG GdcJGH eQLYkG bjekG ddHGMKjf hGdeJNUUjf aj eLGd GdYdGbGJ GdOhdjI hGdCef Gdbhej, ceG Cfg jbOe ddbGQF GdYGe agekG CYeb ddJMOjGJ GdeYGUQI GdJj JhGLg GdCef Ydi GdeSJhi GdEbdjej(B.s
Keywords: (3GdYdGbGJ GdOhdjI (B- (3GdCef GdEbdjejs